Karl Rahner und das Judentum. Updates zu "einem schwierigen Verhältnis" - Collinet, Benedikt Josef (Zeitschrift für neuere Theologiegeschichte, 2025)
Grümme (1997) in particular has criticised Karl Rahner’s relationship to Judaism. Based on Rahner’s Sämtliche Werke , this criticism is re-examined here and placed in the wider context of his work. The article concludes that the previous theses on the dominance of the New Testament over the OT, on the Christocentric doctrine of grace, etc., largely hold up. What is new is the explicit clarification that Rahner was not a racist anti-Semite. This is evident both biographically and in his statements after Auschwitz. His theological position on Judaism is based on (Christocentric) lines of tradition, which he never completely escaped throughout his life. He functionalised Judaism by means of illustrative anti-Judaism as a comparative salvation factor to Christianity. There is hardly any explicit engagement with Judaism. It is therefore not possible for Karl Rahner to develop an independent theology of Israel ("Israeltheologie"). His position is relevant to the history of research and can contribute in future scholarship as a point of reference in Rahner research, in the Catholic approach to Judaism and to the historical reappraisal of (everyday) Christian Jew-Hatred resp. theological antisemitism.